2017
DOI: 10.3945/an.116.013953
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Gastrointestinal Effects of A1 Compared with A2 β-Casein

Abstract: This is the first systematic review, to our knowledge, of published studies investigating the gastrointestinal effects of A1-type bovine β-casein (A1) compared with A2-type bovine β-casein (A2). The review is relevant to nutrition practice given the increasing availability and promotion in a range of countries of dairy products free of A1 for both infant and adult nutrition. In vitro and in vivo studies (all species) were included. In vivo studies were limited to oral consumption. Inclusion criteria encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 50 publications
1
101
2
12
Order By: Relevance
“…41,42 For example, dietary A1 β-casein peptides were associated with inflammatory markers in humans. 43 β-Casein peptides modulated immunoglobulins and cytokines through the gut, but in contrast to our study, effects on IL-6 were not reported. Additionally, multiple protein hydrolysates were found to affect Toll-like receptors (TLRs), but the effects were mostly hydrolysate-dependent rather than focused on individual peptides.…”
Section: Early Clinical Observationscontrasting
confidence: 99%
“…41,42 For example, dietary A1 β-casein peptides were associated with inflammatory markers in humans. 43 β-Casein peptides modulated immunoglobulins and cytokines through the gut, but in contrast to our study, effects on IL-6 were not reported. Additionally, multiple protein hydrolysates were found to affect Toll-like receptors (TLRs), but the effects were mostly hydrolysate-dependent rather than focused on individual peptides.…”
Section: Early Clinical Observationscontrasting
confidence: 99%
“…CSN2 variants play an important role in milk and cheese yield/quality and their concentration is positively associated with good rennet properties of milk (Massella et al, 2017). Moreover, A2 milk (A1 free) is produced in many different countries, claiming its potential benefits in human health (Caroli et al, 2016;Brooke-Taylor et al, 2017), but the studies about positive effects of A2 milk or unfavourable effects of A1 milk are often conflicting. Apart from the contradictory human health studies about CSN2 genotypes (A1/A2), there is still a strong need for the evaluation of corresponding genotype effects on cow fertility and reproduction performance.…”
Section: Discussionmentioning
confidence: 99%
“…This information may be very useful both from a farm health management point of view as well as from a downstream dairy processing point of view. Whole genome sequence data of bulk milk also informs about the herd frequency of functional variants such casein variants affecting consumer health or processing properties 10 , or variants causing inherited defects or embryonic lethality in cows 4 . In many countries, it is not allowed to add milk from cows being treated with antibiotics to the tank.…”
Section: Discussionmentioning
confidence: 99%